High‐Performance Hybrid White OLEDs with Ultra‐Stable Emission Color and Small Efficiency Roll‐Off Achieved by Incorporating a Deep‐Blue Fluorescent Neat Film. Issue 15 (7th May 2021) - Wu, Zilong; Zhu, Xiangyu; Li, Yinghao; Chen, Hao; Zhuang, Zeyan; Shen, Pingchuan; Zeng, Jiajie; Chi, Jiajin; Ma, Dongge; Zhao, Zujin; Tang, Ben Zhong
Abstract: Organic blue luminescent materials play a vital role in the fabrication of full‐color displays and white lighting devices, but high‐efficiency blue emitters that meet commercial demands are still quite insufficient. Herein, the authors wish to report the design and synthesis of four bipolar deep‐blue luminogens consisting of an anthracene core and various functional groups. Their photophysical properties, electronic structures, electrochemical behavior, thermal stability, carrier transport ability, and electroluminescence performance are systematically studied. The nondoped organic light‐emitting diode (OLED) based on DPAC‐TAn‐BI radiates stable deep‐blue light [Commission Internationale de l'Eclairage (CIE x, y ) = 0.15, 0.15] with a high external quantum efficiency (ηext ) of 5.81%. Moreover, efficient two‐color hybrid warm white OLEDs are achieved using DPAC‐TAn‐BI neat film as a blue‐emitting layer, providing an excellent ηext of 27.6%, a small efficiency roll‐off of 2.9% at 1000 cd m −2, and ultra‐stable emission spectra with tiny CIE x, y variation of (0.01, 0.01) from 100 to 10 000 cd m −2 . These results demonstrate that the deep‐blue luminogens are strong candidates for applications in blue and white OLEDs. Abstract : Efficient bipolar deep‐blue luminogens are developed, which can serve as emitters in nondoped deep‐blue OLEDs with external quantum efficiencies (ηext s) of up to 5.81%, and in two‐color hybrid warm white OLEDs with ultra‐stable emission color, an excellent ηext of 27.6%, and a small efficiency roll‐off of 2.9% at 1000 cd m –2 .